Pengaruh Game Online Terhadap Relasi Sosial Para Frater di Seminari Tinggi Interdiosesan St. Petrus, Ritapiret dan Upaya Penyadaran Melalui Pastoral Konseling - Yosef Pehe; Maximus Manu; Fransisco M. Adisaputra; Fransiskus V. Dua; Frederikus D. Veto; Antonius K. Open; Jean Loustar Jewadut (Jurnal Penelitian Pendidikan Agama Katolik, 2025)
Games online usually be used by brothers as an entertainment media. But, excessive use of games online Will have impact on decreasing of social relation which was built by the brothers. This research want to analyze the impact of game online to social relation for the brothers in Major Seminary Interdiocese of Saint Peter Ritapiret. This research also used qualitative method. Data collection techniques used by this research is interviews with key informants. This research, found that excessive use of games online can make negative impact on relation who be built by the brothers. Among them are, alienation in togetherness, the death of empathy, and false act of participation. Besides that, implicitly, game online also have impact to the increase of phubbing phenomenon. To this problems, pastoral counseling was an effective solution offered as a basis for reflection and action to make the brothers aware of the dangers of games online. Pastoral counseling have functions in healing efforts, sustaining, guiding, and reconciling to the brothers influenced by games online.